Quality of life in children undergoing tonsillectomy: a cross-sectional survey - Ying Zhou; Mingqi Peng; Jing Zhou (BMC, 2023)
Abstract Background The quality of life in children undergoing tonsillectomy remains unclear. We aimed to analyze the current status and influencing factors of quality of life in children undergoing tonsillectomy, to provide useful insights to clinical postoperative care for children. Methods Children who underwent tonsillectomy in our hospital from June 1, 2021 to October 31, 2022 were selected. The characteristics of children were collected and Paediatric Quality of Life Inventory Version 4.0 (PedsQL™ 4.0) was used for evaluating the quality of life in children. Pearson correlation, univariate and logistic regression analyses were condcuted to evaluate the influencing factors of quality of life in children undergoing tonsillectomy. Results A total of 118 children undergoing tonsillectomy were included. The total score of PedsQL™ 4.0 in children undergoing tonsillectomy was (70.28 ± 13.15). Pearson correlation analyses indicated that age(r = 0.586), courses of tonsillitis(r = 0.595), parental education level(r = 0.612) and monthly family income(r = 0.608) were associated with the PedsQL™ 4.0 total score in children undergoing tonsillectomy (all P < 0.05). Logistic regression analyses indicated that age ≤ 5y (OR = 2.009,95%CI: 1.826 ~ 2.401), courses of tonsillitis ≥ 3years (OR = 2.167,95%CI: 1.688 ~ 2.547), high school of parental education level (OR = 1.807,95%CI: 1.224 ~ 2.181) and monthly family income ≤ 5000 RMB(OR = 2.624,95%CI:2.092 ~ 3.077) were the independent influencing factors of quality of life in children with undergoing tonsillectomy (all P < 0.05). Conclusions The quality of life of children after tonsillectomy is not high, and the quality of life of children is affected by many factors. Medical staff should take early targeted nursing countermeasures tageted on those influencing factors to improve the quality of life of children.